Asymmetric synthesis of dihydro-1, 3-dioxepines by Rh(ii)/Sm(iii) relay catalytic three-component tandem [4 + 3]-cycloaddition. Issue 15 (15th March 2021) - Xu, Chaoran; Qiao, Jianglin; Dong, Shunxi; Zhou, Yuqiao; Liu, Xiaohua; Feng, Xiaoming
Abstract : Catalytic asymmetric tandem carbonyl ylide formation/[4 + 3]-cycloaddition of β, γ-unsaturated α-ketoesters, aldehydes and α-diazoacetates was achieved by using a bimetallic rhodium(ii )/chiral N, N ′-dioxide–Sm(iii ) complex catalyst. Abstract : Heterocycles have been widely used in organic synthesis, agrochemical, pharmaceutical and materials science industries. Catalytic three-component ylide formation/cycloaddition enables the assembly of complex heterocycles from simple starting materials in a highly efficient manner. However, asymmetric versions remain a yet-unsolved task. Here, we present a new bimetallic catalytic system for tackling this challenge. A combined system of Rh(ii ) salt and chiral N, N ′-dioxide–Sm(iii ) complex was established for promoting the unprecedented tandem carbonyl ylide formation/asymmetric [4 + 3]-cycloaddition of aldehydes and α-diazoacetates with β, γ-unsaturated α-ketoesters smoothly, affording various chiral 4, 5-dihydro-1, 3-dioxepines in up to 97% yield, with 99% ee. The utility of the current method was demonstrated by conversion of products to optically active multi-substituted tetrahydrofuran derivatives. A possible reaction mechanism was provided to elucidate the origin of chiral induction based on experimental studies and X-ray structures of catalysts and products.